Migration-Driven Remittances and Their Role in Boosting Economic Development in Origin Countries - Antonenko, Illia; Shymanska, Kateryna; Mammadov, Orkhan; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This bachelor thesis investigates the role of migration-driven remittances in facilitating economic development and stability in origin countries. By conducting an extensive review of migration and remittance theories, the study identifies key frameworks that explain how remittance flows impact poverty alleviation, investment, and GDP growth. The research utilizes descriptive statistics and panel regression analysis on a dataset of 12 countries over the period 2000–2023 to explore the relationships between remittances, investment, and economic performance. Comparative insights are drawn from different regional contexts to highlight variations in remittance dependency and developmental outcomes. While the findings affirm the positive microeconomic effects of remittances on household welfare and social development, the results also reveal a negative association between remittance inflows and long-term GDP growth, suggesting that remittances alone may not guarantee sustained economic expansion. The study contributes to a nuanced understanding of remittances as a double-edged phenomenon and offers policy recommendations aimed at maximizing their developmental potential while mitigating dependency risks.
Vedoucí práce: Kateryna Shymanska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses